2023
DOI: 10.3390/nu15081918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation of a Microalgae Extract Containing Fucoxanthin Combined with Guarana on Cognitive Function and Gaming Performance

Abstract: Background: Esports competitive gaming requires selective visual attention, memory, quick judgment, and an ability to sustain psychomotor performance over time. Fucoxanthin is a carotenoid, found in specific microalgae varieties such as Phaeodactylum tricornutum (PT), that has been purported to possess nootropic and neuroprotective effects through its anti-inflammatory and antioxidant properties. This study evaluated whether acute and 30-day supplementation of an extract of PT from microalgae combined with gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
(109 reference statements)
0
4
0
1
Order By: Relevance
“…Overall, these data are promising, advocating for the promotion of the microalgae extract of Phaeodactylum tricornutum (PT) as a natural and viable alternative in the dietary supplement arena for improving cognitive function in humans. Notably, Leonard et al (2023) demonstrated that both acute and 30-day ingestion of two different doses of the same microalgae extract of PT tested in the present study, combined with guarana in equal quantities across the experimental groups, improved reaction times, reasoning, learning, executive control, attention shifting (cognitive flexibility), and impulsiveness in e-gamers [ 49 ]. Our research team is currently conducting two clinical studies to evaluate the efficacy of PT microalgae on the cognitive function of healthy elderly individuals (NCT04832412 and NCT05759910).…”
Section: Discussionmentioning
confidence: 92%
“…Overall, these data are promising, advocating for the promotion of the microalgae extract of Phaeodactylum tricornutum (PT) as a natural and viable alternative in the dietary supplement arena for improving cognitive function in humans. Notably, Leonard et al (2023) demonstrated that both acute and 30-day ingestion of two different doses of the same microalgae extract of PT tested in the present study, combined with guarana in equal quantities across the experimental groups, improved reaction times, reasoning, learning, executive control, attention shifting (cognitive flexibility), and impulsiveness in e-gamers [ 49 ]. Our research team is currently conducting two clinical studies to evaluate the efficacy of PT microalgae on the cognitive function of healthy elderly individuals (NCT04832412 and NCT05759910).…”
Section: Discussionmentioning
confidence: 92%
“…Overall, these data are promising, advocating for the promotion of the microalgae extract of Phaeodactylum tricornutum (PT) as a natural and viable alternative in the dietary supplement arena for improving cognitive function in humans. Notably, Leonard et al (2023) demonstrated that both acute and 30-day ingestion of two different doses of the same microalgae extract of PT tested in the present study, combined with guarana in equal quantities across the experimental groups, improved reaction times, reasoning, learning, executive control, attention shifting (cognitive flexibility), and impulsiveness in e-gamers [47]. Our research team is currently conducting two clinical studies to evaluate the efficacy of PT microalgae on the cognitive function of healthy elderly individuals (NCT04832412 and NCT05759910).…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions of symptoms related to dietary supplementation (i.e., dizziness, headache, tachycardia, heart palpitations, dyspnea, nervousness, blurred vision, and others) were assessed using Likert-type scales as previously described [ 52 , 53 ].…”
Section: Methodsmentioning
confidence: 99%